Detection of NDM-1, CTX-M-15 and qnrB4-producing Enterobacter 2 hormaechei isolates in Brazil - Assef, Ana Paula D`a. Carvalho (2014)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Pesquisa em Infecção Hospitalar (LAPIH). Rio de Janeiro, RJ, Brasil.